2004
DOI: 10.1086/380098
|View full text |Cite
|
Sign up to set email alerts
|

Strong Cell‐Mediated Immune Responses Are Associated with the Maintenance of Low‐Level Viremia in Antiretroviral–Treated Individuals with Drug‐Resistant Human Immunodeficiency Virus Type 1

Abstract: Antiretroviral (ARV)-treated patients often maintain low to moderate levels of viremia, despite the emergence of drug-resistant human immunodeficiency virus (HIV). We studied host and viral factors that may contribute to the control of viral replication in a cohort of 189 adults. Among ARV-treated patients with detectable viremia, there was a bell-shaped relationship between Gag-specific CD4+ T cell responses and viremia, with the highest cellular immune responses observed in patients with plasma HIV RNA level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 65 publications
(55 reference statements)
5
64
0
Order By: Relevance
“…One can speculate that vector mobilization resulting in greater antisense pressure against HIV leads to the generation of HIV variants in patients with reduced pathogenicity, which, in combination with the immune reconstituting effects of adoptive cellular therapy, could lead to enhanced control of viral replication. This situation would be reminiscent of the subset of individuals with advanced multidrugresistant HIV that develop an immunologic profile comparable to that of long-term nonprogressors, where it has been suggested that functional immunity can be reconstituted as a result of a de facto attenuated vaccine process that occurs consequent to the generation of drug resistant HIV with reduced fitness (21).…”
Section: Discussionmentioning
confidence: 99%
“…One can speculate that vector mobilization resulting in greater antisense pressure against HIV leads to the generation of HIV variants in patients with reduced pathogenicity, which, in combination with the immune reconstituting effects of adoptive cellular therapy, could lead to enhanced control of viral replication. This situation would be reminiscent of the subset of individuals with advanced multidrugresistant HIV that develop an immunologic profile comparable to that of long-term nonprogressors, where it has been suggested that functional immunity can be reconstituted as a result of a de facto attenuated vaccine process that occurs consequent to the generation of drug resistant HIV with reduced fitness (21).…”
Section: Discussionmentioning
confidence: 99%
“…replicative capacity (10,30); in addition, transient boosting of CD4 ϩ T-cell responses to HIV Gag peptides has been observed after discontinuation of antiretroviral therapy (28). Overall, these observations suggest that an intimate balance prevails in vivo in which antigenic stimulation drives CD4 ϩ T-cell proliferation but is counteracted by destructive effects mediated by HIV.…”
Section: Orous Cd4mentioning
confidence: 90%
“…Subjects were recruited from two established San Francisco cohorts of chronically HIV-infected adults [SCOPE and REACH (12,13); see online supplement]. Subjects were eligible if they were 18 years or older and HIV-antibody positive.…”
Section: Study Populationmentioning
confidence: 99%